Rural And Urban Social Construction Study Regarding Family Planning On The Incident Of Divorce In Banyuwangi District - Mohamad Devan Tri Oktavadhan; Firrial Eksa Maulidania Putri; Dimas Ahmad Nurullah Subekti; Ghani Armando; Syifa'ul Lailiyah; Jayanti Dian Eka Sari (International Journal of Health Engineering and Technology, 2026)
Divorce cases in Indonesia increased by 15.3%, from 447,743 cases in 2021 to 516,344 cases in 2022. Banyuwangi Regency is one of the regions in East Java with a high number of divorce cases, totaling 39,245 divorce certificates. The distribution of divorce cases in Banyuwangi Regency is evenly spread across both rural and urban areas. The objective of this study is to describe the social constructions of urban and rural communities in Banyuwangi regarding family planning in relation to divorce occurrences in Banyuwangi Regency. This study employs a qualitative method with an exploratory study design to describe the social constructions of rural and urban communities regarding family planning in relation to divorce. Data were collected through interviews grounded in Peter L. Berger’s social construction theory. Data analysis was conducted thematically using the Leximancer software. The results of the study indicate that divorce cases occurring in rural and urban areas of Banyuwangi Regency exhibit different social constructions. This is evident in the dimension of motivation for marriage, where in rural areas it is based on the desire to continue the family line, whereas in urban areas it is based on love. The dimension of family resilience is evident in the differences in the division of roles in child-rearing. Divorce in urban communities is viewed as a formal separation, whereas in rural areas it is seen as a matter of incompatibility. Key factors influencing these dimensions include religion, social pressure, and patriarchal practices in both rural and urban communities in Banyuwangi Regency.